Understanding Alzheimer's : an introduction for patients and caregivers - Ali, Naheed, 1981- (Lanham, Md. : Rowman & Littlefield Publishers, Inc., 2015)
"Although every day we read news reports linking health problems to diet and lifestyle, there remains significant confusion regarding the onset and progression of Alzheimer's disease. Worldwide, more than 35 million people are currently suffering from Alzheimer's, and that number is expected to increase substantially over the next decade. Understanding Alzheimer's introduces readers to the inner workings of Alzheimer's, how the disease progresses, and what patients and caregivers can do to live with the disease. Following the astonishing path sufferers take from being sharp-minded to cognitively impaired, the book reveals how patients and their loved ones can cope with its mental, physical, and economic effects. Dr. Naheed Ali sifts through the information currently available on Alzheimer's to clearly and accessibly illustrate how Alzheimer's works, how we can prevent it, and how we can address it once symptoms begin to appear. Covering diet and lifestyle, medical interventions and the stages of Alzheimer's, he draws readers into a fuller understanding of the disease. Providing an accessible starting point for anyone wishing to learn more about Alzheimer's, this book will prove to be an indispensable resource"--Publisher's description.
History of Alzheimer's -- Anatomy, pathology & physiology of Alzheimer's -- Causes of Alzheimer's -- Symptoms of Alzheimer's -- Diagnosing Alzheimer's -- Pharmacological treatment of Alzheimer's -- Natural treatment of Alzheimer's -- The three-stage model of Alzheimer's -- The six-stage model of Alzheimer's -- The seven-stage model of Alzheimer's -- Mental outcomes -- Diseases associated with Alzheimer's -- Pain and Alzheimer's -- Economic effects of Alzheimer's -- Alzheimer's disease research in the US -- Diet and Alzheimer's -- Alzheimer's and exercise -- Finding motivation to cope with Alzheimer's -- Alzheimer's at home.
Includes bibliographical references and index.
Keywords: Alzheimer's disease; Dementia